اثر استعمال إستراتيجية التدريس التبادلي (طرح الأسئلة- التلخيص- التوضيح- التنبؤ) في تحصيل طلاب الصف الرابع الإعدادي الفرع الأدبي في مادة علم الاجتماع. - خضير سكران عرمش, ناصر (Journal of College of Education, 2020)
Aims current research to answer the hypothesis derived there a difference statistically signi ficant when my level of (0.05) in the collection of the fourth grade preparatory students literary  section in the subject of sociology whe are studying on according to strategy Reciprocl teching (ask- questions – summarizing- prediction) and  students who are studing the same material in away Traditional? As it chose resaecher tow division (a-b) tkonan the control group and the experimental and designed a tool consisted of testing after me, That’s the cool of the test measure the collection, and in order to verify the vitural honesty view Rinder cool group of experts and arbitrtors, used researcher Way re- Test to Measure its (stability and after conducting) the test date wera analyzed using appropriate statistical methods as the result showed derived.• The average grades wxperimental group (28.6).• The average group scove zaboth (2049).• No difference statistically significant at the level of (0.05) As the value of the value of tcalauated (6.70) grater than the value spreadsheet (2.000) the superiority of the exrerimental group on the group zabothe , the researcher recommended zero the strategy in the medium and prep schools.